Educação artística como possibilidade de experimentação utópica: o caso da Mindelo Escola Internacional de Arte em Cabo Verde - Denise Perdigao Pereira (2016)
The purpose of this theses it to analyze the field of possiblities of Artistic Education as a place of utopic experimentation, in the sense that it stresses the necessity of developing forms of social life that substitutes the predominat values of the capitalism ethos (MOUFFE: 2007). In this sense, the Mindelo_Escola Internacional de Arte (M_EIA), located in the São Vicente island in Cape Verde, is taken as an analytical unit of the artistic education practices developed not only in the interior of the institution, but also outside of it, for the communities and its populations. The authors Atkinson (2008/2011), Mouffe (2007/2012) and Rancière (2000) are central theorical references for that discussion. The adopted methodological tool consisted in the case study, utilizing diverse sources such as the speeches of vary subjects involved with the school, its political-pedagogical project, the educational programs, the field notes and photographs collected directly during the immersion of the researcher in the place. As a conclusion of the research, there is the presentation of the thesis that the development of an Artistic Education in the counterhegemonic perspective can only happen from the adoption of open artistic and pedagogical practices, which should not be totally controlled, meaning that they should be willing to take risks and to create space for the dissent, fundamental elements for the recreation of reality in its political, social, educative and cultural aspects.